Morphological, phylogenetic and taxonomic studies of Chamaecrista ochnacea Complex (Leguminosae: Caesalpinioideae), a threatened group in the Brazilian Cerrado - Miranda, Késia Ramos; Rando, Juliana Gastaldello (Phytotaxa, 2025)
Chamaecrista is a pantropical genus primarily distributed throughout the Americas, with the Brazilian Cerrado representing its main center of diversity. Based on the morphological variation observed and the phylogenetic reconstruction conducted in this study, a taxonomic reevaluation of Chamaecrista ochnacea was deemed necessary. As a result, we propose two new combinations, four synonymizations, and two lectotypifications. This study contains a morphological characterization, a phylogenetic reconstruction, an identification key, taxonomic notes, photographs, distribution map, updated nomenclatures, typifications, phenological data, and preliminary IUCN conservation assessments.